2018
DOI: 10.1111/aos.13724
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive evaluation of cerebrospinal fluid pressure in ocular hypertension: a preliminary study

Abstract: The wider OSASW and higher estimated CSFP in OH subjects suggest a higher orbital CSFP. Despite a higher orbital CSFP that could be protective, the higher TLCPD in OH may play a significant role in the risk of developing glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…Studies have found that for every 1 mmHg increase in IOP, the risk of glaucoma will increase by 12%, and that for every 1 mmHg interocular difference in IOP the risk of OH transforming into glaucoma increases by 21% ( 2 ). Although not all people with OH will develop glaucoma ( 3 ), Elevated IOP has always been considered the main risk factor for the progression of glaucoma ( 4 ), and it is also the only known modifiable risk factor in the disease ( 5 ), about 9.5% will develop glaucomatous optic nerve damage in their lifetime ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that for every 1 mmHg increase in IOP, the risk of glaucoma will increase by 12%, and that for every 1 mmHg interocular difference in IOP the risk of OH transforming into glaucoma increases by 21% ( 2 ). Although not all people with OH will develop glaucoma ( 3 ), Elevated IOP has always been considered the main risk factor for the progression of glaucoma ( 4 ), and it is also the only known modifiable risk factor in the disease ( 5 ), about 9.5% will develop glaucomatous optic nerve damage in their lifetime ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Third, errors in both displacement and strain could occur. The errors observed here could arise from various sources such as OCT registration errors (intrinsic to the OCT machine), rotation of subjects’ head during OCT acquisition, OCT speckle noise and IOP fluctuations from ocular pulsations, 73 all of which were difficult to control. However, displacement error magnitudes were still lower than the OCT voxel resolution; 20 thus, these errors should not have significantly affected our observed trends.…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, errors in both displacement and strain could occasionally occur. The errors observed here could arise from various sources such as OCT registration errors (intrinsic to the OCT machine), rotation of subjects’ head during OCT acquisition, OCT speckle noise and IOP fluctuations from ocular pulsations, 62 all of which were difficult to control. However, displacement error magnitudes were still lower than the OCT voxel resolution (Appendix C); thus, these errors should not have significantly affected the observed trends.…”
Section: Discussionmentioning
confidence: 99%